2021
DOI: 10.1007/978-981-33-6757-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Mongolian Part-of-Speech Tagging with Neural Networks

Abstract: The purpose of this paper is to present a simple neural networks model-multilayer perceptron for Mongolian part-of speech tagging. We used about 1400 manually tagged sentences for training and testing from Mongolian Penn Treebank. The performance of the model is 80.78% which we consider a promising result. Also, another contribution of this work is that we make our testing data online for the sake of the development of Mongolian part-of-speech tagging research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They concluded that an appropriate size for a Mongolian general corpus is 39-42 million tokens [28]. To tag Mongolian parts of speech (POS), Lkhagvasuren et al utilized a neural network model with a multilayer perceptron [29]. Jaimai and Chimeddorj utilized a hidden Markov model with a bigram [30].…”
Section: Mongolian Nlpmentioning
confidence: 99%
“…They concluded that an appropriate size for a Mongolian general corpus is 39-42 million tokens [28]. To tag Mongolian parts of speech (POS), Lkhagvasuren et al utilized a neural network model with a multilayer perceptron [29]. Jaimai and Chimeddorj utilized a hidden Markov model with a bigram [30].…”
Section: Mongolian Nlpmentioning
confidence: 99%